2016
DOI: 10.1016/j.apenergy.2016.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of jet fuel range alkanes from co-feeding of lignocellulosic biomass with plastics via tandem catalytic conversions

Abstract: Enhanced carbon yields of jet fuel range alkanes were manufactured from cofeeding of lignocellulosic biomass with plastics. The consecutive processes proceeded via the cofeed catalytic microwave-induced pyrolysis and hydrogenation process. In the co-feed catalytic microwave pyrolysis by using ZSM-5 as the catalyst, parent ZSM-5 fabricated by hydrothermal and calcined treatments contributed to the increase of surface area as well as the formation of more mesopores. Liquid organics with enhanced carbon yield (40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(45 citation statements)
references
References 69 publications
1
42
0
Order By: Relevance
“…Click here to download Manuscript Green biorefinery of larch wood biomass.docx Click here to view linked References Gliozzi et al 2014;Ishida et al 2014;Liu et al 2015). In recent year, studies are actively conducted on development the integrated technologies of biomass complex processing (Cherubini et al 2009;Ed de Long et al 2013;Zhang et al 2016;.…”
Section: Manuscriptmentioning
confidence: 99%
“…Click here to download Manuscript Green biorefinery of larch wood biomass.docx Click here to view linked References Gliozzi et al 2014;Ishida et al 2014;Liu et al 2015). In recent year, studies are actively conducted on development the integrated technologies of biomass complex processing (Cherubini et al 2009;Ed de Long et al 2013;Zhang et al 2016;.…”
Section: Manuscriptmentioning
confidence: 99%
“…The maximum yield of bio-oil of ROS1, SSOS, COS, SOS, ROS2, and POS were 65.8%, 57.9%, 58.1%, 60.4%, 60.1%, and 55.3% respectively. The bio-char yields of six soapstocks had no obvious change with different catalytic temperature, they all keep in about 21%, this phenomenon may be related to the ex situ catalysis [24] , since the temperature in microwave reactor was a specific 500°C, the change in external catalyst temperature did not affect biochar production. The coke yields of six soapstocks decreased successively with the increase in catalytic temperature.…”
Section: Analysis Of Pyrolysis Product Distributionmentioning
confidence: 90%
“…Alkanes content of SOS, SSOS, ROS2, COS, cycloalkanes of SOS, SSOS, ROS2, ROS1, COS, and the alkenes, aromatics of all the soapstocks firstly increased and then decreased, reaching the maximum at 300°C. Zhang et al [24] indicated that as the catalytic temperature changes from 249°C to 375°C, the proportion of monocyclic aromatic hydrocarbons of bio-oil in low-density polyethylene increases due to the enhanced hydrogen transfer reaction. When the catalytic temperature exceeded 375°C, the increasing catalytic temperature promoted pyrolysis steam cracking reaction and reducing the aromatic yield.…”
Section: Effect Of Catalytic Temperature On Bio-oil Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the commercial plants, the mineral-based catalysts such as Al 2 O 3 and zeolites have attracted more attentions for the waste oils upgrading [25][26][27]. For example, ZSM-5 is considered to be a promising zeolite-based catalyst for pyrolysis vapor upgrading to produce considerable petrochemicals (e.g., aromatics and olefins) [28][29][30][31]. In our previous work, the zeolite catalysts (e.g., natural zeolite, ZSM-5) were used for the fuel oil production from two-stage pyrolysis-catalytic reforming of brominated high impact polystyrene [32,33].…”
Section: Introductionmentioning
confidence: 99%